The double-edged sword of personality in shaping craftsmanship spirit: an investigation of conscientiousness and openness to experience - Li, Zhi; Lu, Fangmei; He, Gang (Frontiers in Psychology, 2024)
Background: Craftsmanship is associated with various positive outcomes at both individual and organizational level, and thus has attracted scholarly attention on examining its antecedences. While craftsmanship can be shaped by both contextual factors and personal traits, existing research has dominantly focused on the former, leaving the latter less examined. Such a lack of examination limits our understanding of craftsmanship in workplace.Objective: Following the view that individuals' intrinsic desire to do the job as the core of craftsmanship, we define craftsmanship spirit (CS) as an individual's psychological state of feeling competent, transcendent, and valuable during work, which evolves as an individual's skills and knowledge expand. We then draw on the classic dispositional literature to explore how individuals' personality traits (conscientiousness and openness to experience) shape the development of CS differently (i.e., the initial level and the developmental trajectory), and test our theory using a latent growth modeling (LGM) approach.We conducted a four-round on-site questionnaire survey with participants who were employees at a large manufacturing company in China. The final sample consists of 746 matched respondents. Data analysis was performed in Mplus 8.3.Results: Empirical results confirm our hypotheses that both conscientiousness and openness to experience have a positive effect on the initial level of CS (β = 0.48, p < 0.001; β = 0.11, p < 0.01). Besides, conscientiousness has a negative effect on the subsequent growth of CS (β = -0.08, p < 0.001). However, the proposed negative effect of openness to experience on the subsequent growth of CS was not supported when the other four personality traits were considered simultaneously (β = -0.01, p > 0.1).This study reveals that conscientiousness and openness to experience have an important effect on CS. Specifically, both conscientiousness and openness to experience are associated with a high level of CS, and the former is associated with low growth of CS. This study not only broadened our understanding on the antecedences of CS, but also provided a dynamic perspective to understand CS in workplace.